Minutes (extract) : International Solidarity Fund
026-0118-001 144. NCL 25 April 236. INTERNATIONAL SOLIDARITY FUND: Mr. Tewson reported a communication from the Secretaries of the International Solidarity Fund drawing attention to the plight of a considerable number of Spanish Refugees in France, and urging the various National Centres to take such steps as may be possible to secure the dispatch of clothing, boots and shoes, etc., which the French Government had arranged should be admitted free of duty. RESOLVED: "That the Officers should consult with representatives of the appropriate Trade Unions on the matter." 292/946/26/118